Tantangan dan Peluang Implementasi Kurikulum 2013 pada Mata Pelajaran Pendidikan Agama Islam di Era Digital di Sekolah MTs Sa An-Nur Kecamatan Ciseeng-Bogor - Reza Rizkia Kamal; Koko A. Mutolib; Alimudin; Khiarul Umam; Ika Kartika (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Islamic education faces big challenges in adapting to developments in the digital era. This article examines the challenges and opportunities in implementing the 2013 Curriculum on Islamic Religious Education (PAI) subjects in the digital era at the MTS SA An-Nur School, Ciseeng District, Bogor. This research identifies the positive and negative impacts of technology integration in PAI learning, as well as the challenges faced by teachers and students. The main focus of this research is the importance of digital literacy, interactive learning, and curriculum adaptation to meet contemporary cultural needs. Even though digital technology offers various innovations and wider accessibility, it is important to ensure that the integration of this technology remains in accordance with Islamic principles and strengthens Islamic identity in the educational process.